Constituir o Estado, formar a nação : as Cortes de Lisboa e a elaboração do Império do Brasil (1821-1823) - Alexandre Bellini Tasca (2023)
The present thesis aims to verify the hypothesis that the Extraordinary and Constituent General Courts of the Portuguese Nation, in seeking to implement modern constitutionalism, established some of the fundamental pillars for the construction of a Brazilian and independent Nation-state. Although recurrently associated with a “recolonizing” movement of Brazil, the Courts of Lisbon catalyzed the structuring not only of a juridical-administrative body but also of affective and identity ties of the nation incorporated by the Empire of Brazil. This process is analyzed based on the categories of space of experience and horizon of expectations proposed by Reinhart Koselleck. In this key, the Courts of Lisbon are taken as a place for the development of a series of experiences that were socially appropriated in speeches and political practices that were decisive for the learning of citizenship in Brazil. The election of national representatives, parliamentary debates, their publication and circulation were intimately linked to the acceleration of the development of a public sphere, especially in Brazil. Pamphlets and periodicals became important tools to implement plural claims, resulting from the progressive widening of the horizon of possible expectations. Citizenship became the subject of disputes that occupied not only palaces and printed pages but also battlefields throughout Brazil. Although the consolidation of the Empire of Brazil as a national State unfolded over the following decade, this work limited its analysis to the moment of the closing of the General Constituent and Legislative Assembly of the Empire of Brazil in November 1823, when, through violence, the accelerated process of widening citizenship is halted by the decision of the newly acclaimed Emperor of Brazil. However, this action did not nullify the experiences made possible by the Courts of Lisbon, which were fundamental to the development of what we recognize as a civil society, a society that was progressively becoming Brazilian.